The role of public relations education and students’ self-efficacy on career aspiration - Lukman, Syauqy; Koswara, Aang; Sani, Anwar (PRofesi Humas, 2025)
Background: Studies on career readiness and aspiration are crucial for educational establishments to assess how well the education of students influences their self-efficacy. Progress in the Public Relations (PR) profession relies on the successful education of PR academic institutions. Purpose: This study examined the PR students’ self-efficacy by identifying two variables: confidence in their Public relations abilities and skills and confidence in their knowledge of PR. The study then looks at how these predictors affect their career readiness. Methods: Using hierarchical regression, this study looks at the effect of two vital predictors of confidence in PR abilities, skills and knowledge on PR on career readiness. Aside from the two predictors, the demographical characteristics and additional predictors of whether the students have experienced job internships and are currently active in the student association were also examined. The data was analysed using a sample of 139 students from Universitas Padjadjaran. Results: From the regression models, students’ self-efficacy significantly influences career readiness, while having internship experience and being active in student associations are also positively associated with career readiness, although not statistically significant. Demographic characteristics do not have a statistically significant influence on career readiness. Conclusion: This study highlights the non-existent impact of demographic factors on students’ self-efficacy and career readiness while providing underpinnings for future research on self-efficacy. Implication: Although the results may not necessarily reflect similar circumstances in similar settings for other establishments, for the specific context of Universitas Padjadjaran, this study provides data-driven evidence on the role of PR education in the students’ self-efficacy and how they perceive their career aspirations in the future.